Hubungan pengetahuan ibu tentang 1000 HPK, pola asuh, pola makan dengan status gizi usia 36-59 bulan - Ainun Nazihah (UHAMKA PRESS, 2021)
The next-generation quality is determined by growth and development in the golden period (the first thousands days of life). Mother’s knowledge about the first thousand days of life, parenting, and dietary pattern contribute to nutritional status of children. This research aimed to analyze the relationship of mother’s knowledge about the first thousand days of life, parenting, and dietary pattern with nutritional status of children aged 36-59 months at Cilangkahan, Malingping, Lebak-Banten regency in 2020. This research used cross-sectional method. The research involved 56 children aged 36-59 months with a total sampling method. Data taken from July to August 2020. This research based on questionnaires and FFQ. The results are related of mother’s knowledge about 1000 HPK, parenting, and dietary habit with nutritional status of children aged 36-59 months based on Chi-Square (X2) test.